Development and Validation of a Indonesian translate Brief Adolescents Subjective Wellbeing in School Scale - Ahkam Alwi; Dewi Retno Suminar; Nurainy Fardana Nawangsari (Journal of Educational, Health and Community Psychology, 2021)
The purpose of this research is to adapt the Brief adolescents' subjective wellbeing in BASWBSS school and to analyze the psychometric properties of the BASWBSS in Indonesian samples. BASWBSS development consists of two components, namely cognitive and affective. The research subjects were 275 students in four high school schools in Surabaya. The psychometric properties of the items are generally adequate with a good estimate of the loading factor. In the dimension of satisfaction at school, the estimated loading factor is 0.60 to 0.82. The dimension of affect in schools is the estimated value of the loading factor from 0.76 to 0.81. The first-order CFA model showed a good fit with P> 0.05 = 0.046, RMSEA =. 0.047, GFI = 0.94, CFI = 0.99, SRMR = 0.04. Construct reliability on satisfaction at school is 0.887 and the impact dimension at school is 0.762.Â Keywords: satisfaction at school, affect at school, students